SOME BOUNDARY VALUE PROBLEMS FOR FINITE INTEGRABLE VEKUA DIFFERENTIAL EQUATIONS - Čanak, Miloš; Stefanovska, Liljana; Protić, Ljubomir (Matematichki Bilten, 2008)
In this paper some boundary value problems for finite integrable Vekua differential equations are considered and solved by reduction to corresponding boundary value problems for analytic functions with known solving procedure.